The COL27A1 and COL11A1 gene variants are not associated with the susceptibility to anterior cruciate ligament rupture in Polish athletes - Sun, Z.; Bojarczuk, A.; Cieszczyk, P. (Baltic Journal of Health and Physical Activity, 2023)
Introduction Sports injuries are the most common cause of anterior cruciate ligament (ACL) ruptures. Previous research has demonstrated links between some of the COL27A1 and COL11A1 genetic variants and musculoskeletal soft tissue injuries. However, no previous research has investigated the COL27A1 rs1570460 and the COL11A1 rs3753841 in the context of ACL rupture in any population. Thus, our study aimed to assess the association between specific single nucleotide polymorphisms (SNPs), i.e., COL27A1 rs946053 and COL11A1 rs3753841, and the occurrence of ACL injury (ACL-I) in a cohort of Polish athletes.